The Influence of Job Equivalency Implementation on the Career Patterns of Functional Officials at the Institut Seni Indonesia Yogyakarta: The Role of Performance as a Mediating Variable - Supiyarto, Edy; Subyantoro, Arief; Hikmah, Khoirul (Multidiscience : Journal of Multidisciplinary Science, 2025)
This study aims to analyze the implementation of job equivalency on career patterns of functional officials at the Institut Seni Indonesia (ISI) Yogyakarta, with performance as a mediating variable. Job equivalency is a strategic policy in bureaucratic reform that aims to improve organizational efficiency and effectiveness. However, implementing this policy often faces challenges, especially in the development of career patterns of functional officials. This study uses a quantitative approach with a path analysis method to measure the relationship between the implementation of job equivalency, career patterns, and performance. Data were obtained through a survey of functional officials at ISI Yogyakarta, which was analyzed using statistical tools. The results of the study indicate that the implementation of job equivalency significantly affects functional officials' career patterns. In addition, performance is a variable that mediates the influence between job equivalency and career patterns. These findings provide important implications for strategic decision-making in human resource management, especially in the scope of Institut Seni Indonesia (ISI) Yogyakarta.